Libraries Address The Challenges Of Asynchronous Learning - Eustis, Joanne; McMillan, Gail (Online Learning, 1998)
As asynchronous learning becomes the norm throughout academia, changes are taking place in campus information systems. Academic libraries, as the entity responsible for serving the information needs of the university, have little choice but to change dramatically. In fact, academic libraries have a history of being aggressive in adapting state-of-the-art technologies. One can point to decades-long involvement with the development of online catalogs and the use of shared cataloging utilities. Libraries continue to serve academic teaching and learning by taking on new roles, revising traditional services, and time and space constraints. Libraries have, however, been slower to adjust organizational structures and processes to leverage the potential of technology. Replies to a recent survey of Association of Research Libraries (ARL) indicate that change in the responding libraries at this time is incremental rather than dramatic. Patterns are emerging, however, relative to resource reallocation and the formation of partnerships with other university units that reflect new priorities. This article describes two examples of innovative information delivery initiatives. VIVA, the Virtual Library of Virginia, was proposed by the state’s Library Advisory Council in 1993 to encourage collaboration among the Commonwealth’s institutions of higher education and to support the electronic dissemination of information. Academic libraries are also leading the way by providing new and unique sources of online information such as Electronic Theses and Dissertations (ETDs), by developing electronic submissions, online archiving, and Web access, as well as bringing to the forefront discussions about issues such as copyright and publishers’ control of academic publications. Network-based access to information resources such as these is changing higher education, and the opportunities offered by asynchronous learning networks are challenging libraries to adjust their policies, processes, and services.